Mesenchymal Stem Cell - Derived Exosomes: New Opportunity i n Cell - Free Therapy - Davod Pashoutan Sarvar; Karim Shamsasenjan; Parvin Akbarzadehlaleh (Tabriz University of Medical Sciences, 2016)
Mesenchymal stromal/stem cells (MSCs) are involved in tissue homeostasis through direct cell - to - cell interaction, as well as secretion of soluble factors. Exosomes are the sort of soluble biological mediators that obtained from MSCs cultured media in vitro. MSC - deriv ed exosomes ( MSC - DEs ) which produced under physiological or pathological conditions are central mediators of intercellular communications by conveying proteins, lipids, mRNAs, siRNA, ribosomal RNAs and miRNAs to the neighbor or distant cells. MSC - DEs have been tested in various disease models, and the results have revealed that their functions are similar to those of MSCs. They have the supportive functions in organisms such as repairing tissue damages, suppressing inflammatory responses, and modulating the immune system. MSC - DEs are of great interest in the scope of regenerative medicine because of their unique capacity to the regeneration of the damaged tissues , and the present paper aims to introduce MSC - DEs as a novel hope in cell - free therapy.